Characteristics of Blood Lipid Profile in Patients with Reactive Arthritis with Disturbance of Microbiocenosis of the Gastroduodenal Zone and Ways of its Correction - Azadaeva K. E.; Tukhtaeva N. Kh.; Karimov M. Sh. (Scholars Digest Publishing, 2023)
The purpose of the study was to study lipid metabolism in patients with reactive arthritis with impaired microbiocenosis of the gastroduodenal zone and to evaluate the clinical possibilities of probiotics in order to correct disorders of the microbiocenosis of the gastroduodenal zone and metabolic disorders. Material and methods: 200 patients with reactive arthritis with microbiocenosis of the gastroduodenal zone were taken for the study. Results: Based on the data obtained, it can be concluded that the addition of drugs that improve the state of intestinal microbiocenosis to the standard treatment regimen for reactive arthritis in violation of the lipid spectrum contributes to the normalization of the lipid profile in this category of patients.
Keywords: Reactive arthritis, lipid profile, microbiocenosis, dyslipidemia.